LO038: Evaluation of a midstream urine collection technique for infants in the emergency department. (2nd June 2016) - Crombie, T.; Slinger, R.; Barrowman, N.; McGahern, C.; Smith, L.; Chu, J.; McCoy, K.; Akiki, S.; Plint, A.
Abstract : Introduction: A novel bladder stimulation technique has been described for midstream urine (MSU) collection in well-feeding, inpatient newborns. We sought to determine the performance of this technique amongst infants presenting to the Emergency Department (ED).Methods: Our prospective ED-based study enrolled a convenience cohort of infants aged ≤ 90 days who required urine testing. Infants with significant feeding issues, moderate to severe dehydration, or critical illness were excluded. Bladder stimulation consisted of finger tapping on the lower abdomen with or without lower back massage while holding the child upright. Healthcare providers received standardized training in the technique. Primary outcome was the proportion of infants with successful MSU collection via the technique. Success was defined as adequate sample collection (≥ 1 mL urine) within 5 minutes of initiating stimulation. Secondary outcomes included the proportion of contaminated MSU samples, time required for MSU collection and full protocol completion, and patient discomfort as perceived by parent/guardian using a 100 mm visual analog scale [VAS]. Assuming success a priori in 50% of infants, a sample size of 115 allowed a 95% confidence interval of +/- 9.1% around the point estimate.Results: We enrolled 115 infants. Mean age was 53.0 days old (interquartile range [IQR] 26.7-68.0); 58.3% were male (69.2% uncircumcised). Midstream urine was successfully collected in 61 infants (53.0%; 95% CI 0.44, 0.62). Thirty-one MSU samples (50.8%) were contaminated; uncircumcised males held the highest proportion (55.0%). Most contaminated samples (83.9%) were reported as "non-significant growth" or "growth of ≥ 3 organisms" and were easily identifiable as contaminants with minimal impact on clinical care. Only 4 (8.5%) of the 47 patients discharged home after successful MSU collection had a repeat ED visit for urine testing. Median stimulation time for MSU collection was 45 seconds (IQR 20-99 secs). Median time for full protocol completion was 30.83 minutes (IQR 24.42-46.83 mins). Mean VAS for infant discomfort was 20.2 mm (SD +/- 20.4 mm).Conclusion: Our pragmatic, ED-based study found the success rate of this bladder stimulation technique to be significantly lower (53%) than its published rate (86%). The contamination rate was high but most contaminated specimens were easily identifiable as such and had minimal clinical impact.